The Perspective of Psychosomatic Medicine on the Effect of Religion on the Mind-Body Relationship in Japan - Nakao, Mutsuhiro (Journal of religion and health, 2014)
Shintoism, Buddhism, and Qi, which advocate the unity of mind and body, have contributed to the Japanese philosophy of life. The practice of psychosomatic medicine emphasizes the connection between mind and body and combines the psychotherapies (directed at the mind) and relaxation techniques (directed at the body), to achieve stress management. Participation in religious activities such as preaching, praying, meditating, and practicing Zen can also elicit relaxation responses. Thus, it is time for traditional religions to play an active role in helping those seeking psychological stability after the Great East Japan Earthquake and the ongoing crisis related to the nuclear accident in Fukushima, Japan, to maintain a healthy mind-body relationship.